2000
DOI: 10.1016/s0393-0440(99)00036-4
|View full text |Cite
|
Sign up to set email alerts
|

Single-sided domain walls in M-theory

Abstract: We describe some single-sided BPS domain wall configurations in M-theory. These are smooth non-singular resolutions of Calabi--Yau orbifolds obtained by identifying the two sides of the wall under reflection. They may thus be thought of as domain walls at the end of the universe. We also describe related domain wall type solutions with a negative cosmological constant.Comment: 38 pages, LaTe

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(63 citation statements)
references
References 38 publications
2
61
0
Order By: Relevance
“…The solution has a singularity at y = 0. In [11], it was shown that the metric (5) is the asymptotic form of a complete non-singular hyper-Kähler metric on the complement in…”
Section: The Basic Domain-wall Constructionmentioning
confidence: 99%
See 3 more Smart Citations
“…The solution has a singularity at y = 0. In [11], it was shown that the metric (5) is the asymptotic form of a complete non-singular hyper-Kähler metric on the complement in…”
Section: The Basic Domain-wall Constructionmentioning
confidence: 99%
“…Since the BPS solutions partially break supersymmetry, while retaining a certain number of Killing spinors, it follows that the Ricci-flat metrics will have special holonomy. In [9,10,11], a geometrical interpretation of these domain walls as Ricci-flat spaces with toroidal fibre bundle level surfaces was given.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, if H(z) is piecewise continuous, it describes domain walls sited at the discontinuous points. Such solutions have been discussed in [18,19,20,21,22]. Another possibility is to consider the case in which, H(z) is piecewise continuous and periodic 2 .…”
Section: Exponential Hierarchy In Gauged Supergravitymentioning
confidence: 99%